Magnetic stimulation in the microscale: the development of a 6 × 6 array of micro-coils for stimulation of excitable cells in vitro. (22nd January 2018) - Rizou, M E; Prodromakis, T
Abstract: In this study we present the development of a prototype device, designed for micro-magnetic stimulation of excitable cells in vitro . Each platform consists of a 6 × 6 two-dimensional array of micro-coils, in an attempt to achieve highly localised magnetic flux patterns. The coils are fabricated with standard micro-fabrication techniques, including steps of photolithography, dry etching and electroplating. The further interfacing of the micro-magnetic chip into a biocompatible platform is also described. The samples are characterised electrically, while a finite element method simulation study is performed and reveals a 141 mV-strong electric potential induced in the vicinity of a micro-coil. Since applications in neuronal cells is our primary focus, modelling with NEURON software is used for demonstrating the capability of the platform to activate adjacent cells. Finally, an experimental validation of the proof of concept is performed with the measurement of induced current into a custom-made phantom gel that shows similar electric properties with brain tissue.